Capsaicin analogue supplementation does not improve 10 km running time-trial performance in male amateur athletes: A randomized, crossover, double-blind and placebo-controlled study - von Ah Morano, Ana Elisa [UNESP]; Padilha, Camila S. [UNESP]; Soares, Vinicius Aparecido Matos [UNESP]; Machado, Fabiana Andrade; Hofmann, Peter; Rossi, Fabrício E. [UNESP]; Lira, Fábio Santos [UNESP] (MDPI, 2021)
Background: To investigate the acute effects of a capsaicin analogue supplement on 10 km time-trial performance and physiological responses in amateur athletes. Methods: Twenty-one participants (age = 29.3 ± 5.5 years, weight 74.2 ± 11.3 kg, height 176.0 ± 0.0 cm, fat mass . 12.7 ± 3.8%, VO2max 62.7 ± 8.4 mL·k−1·min−1 ), completed two randomized, double-blind trials: capsaicin analogue condition (Capsiate (CAP) = 24 mg) or a placebo (PLA) condition. The participants consumed two doses of 12 mg of CAP or PLA capsule 45 min before and immediately at the start of each trial. The time required to complete 10 km, lactate concentration, maximum heart rate (HRpeak ), and rating of perceived exertion (RPE) were recorded. Results: The 10 km time-trial performance (CAP = 45.07 ± 6.41 min vs. PLA = 45.13 ± 6.73, p = 0.828) was not statistically significantly different between conditions. No statistically significant differences between conditions were detected for lactate concentration (p = 0.507), HRpeak (p = 0.897) and RPE (p = 0.517). Conclusion: Two doses of a 12 mg Capsaicin analogue supplement did not improve performance and physiological responses in a 10 km running time-trial in amateur athletes.
Keywords: Ergogenic aid; Pepper; Running races